Vampires do hunt marshmallow bunnies : The Bailey School Kids Jr. Chapter Book - Marcia Thornton Jones, Debbie Dadey (New York, NY : Scholastic, 2008)
Oh, no! Something is happening to all of the candy in Bailey City. Will they still be able to have the Easter egg hunt?
380